Sonic multiplicities : Hong Kong pop and the global circulation of sound and image - Chow, Yiu Fai (Intellect, 2013)
'Sonic Multiplicities is a fascinating book, with essays rich in empirical detail and - captivatingly combining the personal and the theoretical - evocative of the complexities of experience, desire and politics in our perplexingly mobile and entangled world. The book's focus on Hong Kong pop music as part of a translocal, if not global network of flows provides a starting point for the authors to unsettle received notions of Chineseness, place and identity, of particular importance in a time when we need to come to terms with, and resist, the increasingly stifling discourse of "the rise of Ch.